American eel personality and body length influence passage success in an experimental fishway. Issue 12 (7th September 2021) - Mensinger, Matthew A.; Brehm, Allison M.; Mortelliti, Alessio; Blomberg, Erik J.; Zydlewski, Joseph D.
Abstract: Millions of dams impair watershed connectivity across the globe and have severely affected migratory fish populations. Fishways offer upstream passage opportunities, but artificial selection may be imposed by these structures. Using juvenile American eel Anguilla rostrata as a model species, we consider whether individual differences in behaviour (i.e. personality) and fish size can predict passage success. We evaluated the expression of bold and exploratory behaviours using open field and emergence assays in the laboratory. Then we assessed the propensity for individuals to volitionally climb through an experimental fishway to understand if personality and fish size could predict climbing success. We demonstrate personality in juvenile eels, and swimming speed in the open field was negatively associated with climbing propensity. Slower swimmers were up to 60% more likely to use the passage device suggesting that more exploratory eels incurred greater passage success. For successful climbers, climbing time was negatively associated with fish length. Synthesis and applications . Our results suggest fish may segregate at barriers based on personality and size. Preventing a subset of individuals from accessing upstream habitat is likely to have negative consequences for fish populations and aquatic ecosystems. Selection may be alleviated by increasing passage opportunities, maximizing fishway attraction and avoiding inefficient passage solutions. Abstract : Our results suggest fish may segregate at barriers based on personality and size. Preventing a subset of individuals from accessing upstream habitat is likely to have negative consequences for fish populations and aquatic ecosystems. Selection may be alleviated by increasing passage opportunities, maximizing fishway attraction and avoiding inefficient passage solutions.